Participation and environmental assessment in Northern and Southern cities, with examples from Stockholm and Jakarta. (1st January 1999) - McGranahan, Gordon; Gerger, Asa
Increasing public participation in environmental assessment is a common goal, North and South. Despite a relative lack of formal education and institutionalised democracy, participatory appraisal has become far more popular in low-income areas in the South, where many advocates claim that it is possible to give local residents a large measure of control over both the research process and its follow-up. In the urban context, the potential for participatory environmental assessment is related to the spatial extent of the environmental challenges. The most critical environmental problems in Southern cities tend to be local, while the most critical environmental problems for Northern cities tend to be global. Using examples from Stockholm and Jakarta, this paper illustrates how such differences alter the comparative advantages of expert and lay knowledge, and the forms of participation that can realistically be aspired to.